Training needs Based on Knowledge Economy Standards for Arabic Language Teachers in North-Eastern Badia Directorate of Education - AL-shurafat , Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present study aimed at investigating the perspectives of Arabic Language teachers in North-eastern Badia Directorate of Education of their training needs based on their knowledge of economy standards. The variables of the study are gender, qualification and years of experience. The population of the study consisted of 300 male and female teachers randomly chosen from the North-eastern Badia Directorate of Education. The researcher has developed a questionnaire to be the instrument of this study. This questionnaire consisted of 5 domains: outcomes, content, learning and teaching strategies, students and assessment. The findings of the study showed that there are significant differences at0.05 ≥ α in all the domains of the questionnaire. Significant differences were also found in the domains of outcomes, strategies and assessment in favor of the variable of experience less than 10 years on the rank 5-10 years of experience. In the variable of content the differences were also in favor of the experience less than 5 years in the rank 5-10 years of experience. Furthermore, the findings of the study showed significant differences at 0.05 ≥ α on the domain of students in favor of less than 5 years of experience. Finally, the findings of the study showed significant differences in favor of males in all the domains of the questionnaire and in favor of the females in the domains of assessment and students.